Field emission investigation of composites of polypyrrole with graphene oxide, reduced graphene oxide and graphene nanoribbons - Harpale, Kashmira; Bansode, Sanjeewani; More, Mahendra; Late, D. J. (2016 29th International Vacuum Nanoelectronics Conference (IVNC), 2016)
The monomer pyrrole has been polymerized by chemical route in the presence of graphene oxide (GO), reduced graphene oxide (rGO) and graphene nanoribbons (GNR) separately to prepare nanocomposites as Polypyrrole-GO (PGO), PPy-rGO (PRGO), PPy-GNR (PGNR), respectively. The morphological, chemical and structural characterization of the as-synthesized products was carried out using scanning electron microscopy (SEM), Raman and fourier transform infrared (FTIR) spectroscopy. Field emission (FE) studies of PGO, PRGO, PGNR emitters were performed at the base pressure of 1x10(-8) mbar in planar `diode' configuration. Onset and threshold field values corresponding to emission current densities of 1 and 100 mu A/cm(2) are observed to be 1.5 and 2.3V/mu m for PGO, 1.4 and 2.2 V/mu m for PRGO and lowest for PGNR as 0.9 and 1.2V/mu m, respectively. The maximum emission current density of 2.5 mA/cm(2) drawn for PGO at the applied electric field of 3.2V/mu m, 1.2 mA/cm(2) at 3.6V/mu m from the PRGO and 8 mA/cm(2) at the field of 2.2 V/mu m from the PGNR emitters. An emission current versus time (I-t) plot shows stable emission behavior for the preset current values.
Keywords: field emission; FTIR; polypyrrole; Raman